"It's just in that sea of things that I never cared about": perception of hepatitis B amongst university students in Aberdeen, North-East Scotland - Emma L. Davies; Shona Fielding; Gillian Noble; Emmanuel Okpo (BMC, 2019)
Abstract Background A significant proportion of international students at UK universities are from regions with medium to high hepatitis B prevalence rates. Understanding the perception of students regarding hepatitis B infection is crucial for the development of appropriate information and services for this population group. Methods Twenty semi-structured interviews were conducted with students from the University of Aberdeen. The following key areas were covered: knowledge, awareness, practices including testing, cultural and social aspects and general attitudes to health information and services. Interviews were transcribed verbatim and coded using a framework analysis approach. Results The participants acknowledged hepatitis B to be a serious disease yet did not consider themselves to be at risk. They felt able to go to their General Practitioner if concerned about hepatitis B but emphasised that there was no indication that this was required. There was a general lack of knowledge about the disease including confusion over other types of hepatitis. This was linked to the perceived lack of attention given to hepatitis B in, for example, sexual health education and disease awareness raising campaigns. The participants expressed a desire for information on hepatitis B to be relevant to the student population, easy to understand, socially acceptable and easily accessible on student portals and social media platforms. Conclusions Our study suggests that students in Aberdeen, North East Scotland lack knowledge and awareness of hepatitis B and do not perceive themselves as being at risk of hepatitis B infection. There is a need for more tailored hepatitis B messages to be incorporated into a range of contexts with clearer risk communication for the student population.